ped SNP file for polar bears of the Hudson Bay region - Viengkone, Michelle; Derocher, Andrew Edward; Richardson, Evan Shaun; Malenfant, René Michael; Miller, Joshua Moses; Obbard, Martyn E.; Dyck, Markus G.; Lunn, Nick J.; Sahanatien, Vicki; Davis, Corey S. (Dryad Digital Repository, 2016)
The following file (.ped) contains SNP data (3341) for 414 individual bears sampled in the Hudson Bay region. Each bear has a unique bear ID (see second column) and is also categorized by the subpopulation in which it is designated to (see column one). Columns three and four indicate the ancestry of the individual (parents) and are followed by the individual's sex (coded: 1 = male, 2 =female). The remaining columns are the individual's genotype.